Profitabilitas Memoderasi Pengaruh Financial Distress pada Opini Audit Going Concern - Oka Maheswara, Anak Agung Gde; Dwirandra, A.A. Ngurah Bagus (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine the effect of partial financial distress on the going concern audit opinion, to determine the effect of partial profitability on the going concern audit opinion and to know the moderating ability of profitability on financial distress that affects the going concern audit opinion. This research conducted at manufacturing companies listed on the Stock Exchange in 2015-2017. The research sample was obtained using purposive sampling technique. Data collection is done by non-participant observation methods. Data analysis techniques are carried out using the method of binary logistic regression analysis. The test results show that financial distress has an effect on the going concern audit opinion, profitability has no effect on the audit opinion, and profitability weakens the effect of financial distress on the going concern audit opinion. Keywords : Financial Distress; Going Concern Audit Opinion; Profitability.